Discontinuous carrier-based SVPWM strategies for three-phase voltage source inverter controlling asymmetrical two-phase induction motors - Srirattanawichaikul W. (2017)
© 2016 The Institute of Electrical Engineers of Japan. This paper presents a discontinuous carrier-based space vector pulsewidth modulation (CB-SVPWM) strategy for three-phase voltage source inverter (VSI) fed asymmetrical two-phase induction motor (TPIM) drives. The proposed modulation technique is based on the general equation of the zero-sequence voltage injection signal in the modulation signals for the drive's TPIM scheme. This technique enables to reduce the average switching losses of the power devices and improve the performance of the TPIM. The viability and performance of the proposed modulation strategy is verified through both simulation and experimental results, which are demonstrated to provide the capability and stability of the proposed system.